Polish Independent Press Summary, no. 21 (1988) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
A digest of Polish underground press (including articles, tables of content, and book covers) compiled by members of the RFE Polish Underground Publications Unit to be used in a daily 20-minute broadcast on Polish samizdat. Extract from Tygodnik Mazowsze, no. 239 (17 February 1988). Extract from Przegląd Wiadmości Agencyjnych, no. 7 (17 February 1988). Extract from Tu Teraz, no. 62 (December 1987). Extract from Gazeta Podziemna, no. 13 (December 1987). Extract from Dokumenty i Informacje, no. 22 (21 February 1988). Table of Contents from Alternatywa, no. 2 (1987).